Pengembangan LKPD HOTS Bernuansa Kemandirian Belajar pada Materi Perkalian dan Pembagian Pecahan Kelas V Sekolah Dasar - Ririn Ririn; Bistari Bistari; Asmayani Salimi; Hamdani Hamdani; Dyoty Auliya Vilda Ghasya (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2023)
This study aims to produce nuanced HOTS LKPD products independent learning on multiplication and division of fractions for class V School decent basis. the research method used is research and development (RnD) by adapting the Thiagarajan 4D development model(define, design, development, and dissemination). The data source of this research is the results of the validation of the three validators, the results of the student response questionnaire, as well as the results of the tryouts student worksheets. The data collection technique for this research is a questionnaire validator validation, response questionnaire, test questions for students, as well as documentation on the LKPD used by the teacher. The results of the research show that during the process of developing LKPD HOTS with the nuances of learning independence is carried out only in three stages, namely the define stage, design stage, and development (development). the validity of the average percentage of LKPD aspects learning (material) of 3.83 with very valid criteria from the language aspect of 3.84 with very valid criteria, from a technical/appearance aspect of 3.9 with very valid criteria, and from the aspect of conformity with the nuances of independence learning of 3.8 with very valid criteria. Next, the result of the response small-scale students get an average percentage of 79.42% with good criteria and large-scale tests obtained an average percentage of 89.23% with very good criteria.